Temporal analysis of environmental noise and air pollution nearby a government hospital in Suburban Klang Valley, Malaysia - Helmi, Amirul Aiman; Ezani, Nur Eliani; Syed Ismail, Sharifah Norkhadijah; Rasdi, Irniza (Universiti Putra Malaysia, 2021)
Introduction: Exposure to ambient noise and air pollution from road traffic has been associated with an increased risk of adverse health effects, such as heart disease and mental health. Although recent studies have identified tem- poral variations of noise and air pollution in urban areas, there has been limited data on the levels within sensitive areas such as a hospital. Thus, this study presents the scenario of noise and air quality level in the temporal dimen- sion assessed near a hospital located in the suburban area of Klang Valley, Malaysia. Methods: A-weighting noise level (dBA) 3M™ Edge™ 5 Personal Noise Dosimeter and PM2.5 concentration Dusttrak II Handheld Aerosol Monitor Model 8523 (μg/m3) were measured simultaneously with a 1-min interval. All measurements were taken from 0700 hrs until 1900 hrs on weekdays and weekends. Results: High noise level (min= 61.1 dBA, max= 62.0 dBA) and PM2.5 concentrations (min= 20 μg/m3, max= 29 μg/m3) were observed during morning peak hours on weekdays and weekends. Noise levels measured are exceeded the Department of Environment (DOE) guideline limit (55 dBA) and PM2.5 concentrations complied with the annual standard (35 μg/m3). We observed moderate correlations between noise and particulate pollution PM2.5 during weekdays and weekends (r= 0.66, p<0.01). Conclusion: Noise level and PM2.5 concentration varied widely over time and could have a negative impact on human health. Our case study rec- ommends that measurement of both noise and air pollution deserved further investigation to allow detailed exposure characterisation of this relationship.